Prediction of Left Main Coronary Artery Occlusion by ST Segment Elevation in Lead aVR Greater than that in Lead V1 in Acute Coronary Syndrome - Ahemd, Abdul Azeez; Ali, Mahboob; Majumder, Abdullah Al Shafi; Ali, M Atahar; Patwary, Md Shafiqur Rahman; Rahman, Mohammad Arifur (Cardiovascular Journal, 2017)
Background: The electrocardiogram (ECG) predicting an acute obstruction of the LMCA, which requires immediate aggressive treatment, is very important for early diagnosis. We correlated ST segment elevation in lead aVR greater than that in lead V with coronary angiographic diagnosis of LMCA occlusion in patients with acute coronary syndrome. Methods: Cross sectional analytical study was conducted in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh from August 2011 to July 2012. Total 90 patients were included purposively. Study population was divided into two groups. Group I- Patients with ST segment elevation in aVR greater than ST segment elevation in V (n=45) and group II- Patients with ST segment elevation in aVR less than that in lead V (n=45). In hospital outcomes were observed for cardiogenic shock, left ventricular failure, hypotension, arrhythmia and death. Results: Acute LVF was significantly (P<0.05) higher in group I but other complications were not significant (P>0.05) between two groups. LM involvement was significantly higher in group I (91.1% vs. 20.0%, p<0.05). ST segment elevation in aVR greater than ST segment elevation in V (n=45) for prediction of LM significant disease has got a sensitivity of 82.0%, specificity 90.0%, accuracy 85.6%, positive and negative predictive values were 91.1% and 80.0% respectively. Conclusion: ST segment deviation in lead aVR greater than that in lead V1 is supposed to be a positive predictor of left main coronary artery obstruction with highly sensitivity and accuracy. Precordial leads V1 and V6 can also predict the critical LMCA obstruction in patients with acute coronary syndrome. Cardiovasc. j. 2017; 9(2): 77-82